Factors influencing medication compliance towards the recovery of pulmonary tuberculosis patients in the passo health center work area - Corputty, Lintje Sintje; Latuamury, Sitti R; Nurhidayati, Siti; Bugis, Nova; Thalib, Abdul (Innovative Approaches in Health Science Journal, 2024)
Introduction: Pulmonary tuberculosis is an infectious disease that requires long-term treatment with high compliance. Compliance in taking medication is a key factor that affects the recovery of tuberculosis patients. In the Passo Health Center work area, it is important to understand the factors that influence this compliance in order to improve treatment outcomes. Method: This study used a quantitative method with a cross-sectional analytical survey design conducted in November 2023. The study population consisted of 40 pulmonary tuberculosis patients undergoing OAT treatment. The total sampling technique was used to collect samples, with a purposive sampling approach based on certain criteria. Results: The results showed that 75% of patients had good knowledge about their disease. As many as 87.5% of patients received good family support, and 75% of patients were always supervised in taking medication. However, only 62.5% of patients were compliant in taking medication as recommended. Factors such as lack of knowledge (25%), inadequate family support (12.5%), and lack of supervision in taking medication (25%) contribute to non-compliance, which in turn can lead to therapy failure and drug resistance. Conclusion: Compliance of pulmonary tuberculosis patients in treatment is greatly influenced by knowledge, family support, and supervision of taking medication. Interventions that focus on improving education, strengthening family support, and stricter supervision in treatment are needed to improve healing and prevent drug resistance.